THE CONCEPT OF FEAR IN THE LITERARY FAIRYTALE - Дибовська, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of researches of fear, especially in literary fairytales. Specific features of presence of fears in chronotope and their classification are defined. Modern popular subgenres of terror literature as horror, suspense, thriller are delineated. The condition of existence of fear in children’s literature is analyzed.